Potential role of SIRT1 in cell ferroptosis - Yueming Zhang; Fanxiao Kong; Nan Li; Lina Tao; Jinghui Zhai; Jie Ma; Sixi Zhang (Frontiers in Cell and Developmental Biology)
Ferroptosis is a novel form of cell death that uniquely requires iron and is characterized by iron accumulation, the generation of free radicals leading to oxidative stress, and the formation of lipid peroxides, which distinguish it from other forms of cell death. The regulation of ferroptosis is extremely complex and is closely associated with a spectrum of diseases. Sirtuin 1 (SIRT1), a NAD + -dependent histone deacetylase, has emerged as a pivotal epigenetic regulator with the potential to regulate ferroptosis through a wide array of genes intricately associated with lipid metabolism, iron homeostasis, glutathione biosynthesis, and redox homeostasis. This review provides a comprehensive overview of the specific mechanisms by which SIRT1 regulates ferroptosis and explores its potential therapeutic value in the context of multiple disease pathologies, highlighting the significance of SIRT1-mediated ferroptosis in treatment strategies.